Relationship Between the Age and Sex of the Patient With the Results of the Indirect Immunofluorescence Test in Patients With Bullous Dermatoses - Ninković Baroš, Đuka; Balaban, Jagoda; Umičević-Šipka, Sanja; Gajanin, Vesna (Scripta Medica, 2022)
Background/Aim: Autoimmune bullous diseases are characterised by the production of autoantibodies to epidermal or subepidermal adhesive proteins. The aim of this study was to determine the relationship between age and sex of patients with the results of indirect immunofluorescence test in patients with newly diagnosed bullous dermatoses. Methods: The investigation presents a retrospective study of newly diagnosed patients with autoimmune bullous diseases at the Clinic for Skin and Venereal Diseases of the University Clinical Centre in Banja Luka in the period 2016-2021. In addition to demographic data, the results of an indirect immunofluorescence test in two titres (≥ 1:10 and ≥ 1:100) were analysed. Results: In this study, almost the same number of patients with pemphigus (45.2 %) and pemphigoid (54.8 %) was found. There were more women than men in the total sample (p = 0.049). The average age of subjects with pemphigoid was higher than that of patients with pemphigus (p = 0.001). 48.2 % of patients with pemphigus and 51.8 % of patients with pemphigoid had a positive indirect immunofluorescence test. A positive test for epidermal intercellular substance in both sexes at a titre ≥ 1:100 is higher than a titre ≥ 1:10 (p = 0.029). Patients with autoantibody titres ≥ 1:100 to desmoglein-1 were statistically significantly older than patients with titres ≥ 1:10 (p = 0.047). Conclusion: Number of patients with pemphigus and pemphigoid were similar, with no difference in sex distribution between the two groups of patients, but patients with pemphigoid were older than patients with pemphigus. The difference between high and low autoantibody titres in both sexes was found only in the group of pemphigus on epidermal intercellular substance and desmoglein-1.